Agricultural value chain development in Nepal: Understanding mechanisms for poverty reduction. (12th January 2022) - Kafle, Kashi; Songsermsawas, Tisorn; Winters, Paul
Abstract: This analysis investigates the potential mechanisms and the practical significance of agricultural value chain development in a geographically challenging rural area of a developing country. Using data from a carefully designed primary survey administered in a hill and mountainous region in Western Nepal, we show that linking small‐scale producers to regional and local traders can help increase income. Analysis of impact pathways shows that the positive impact on household income emerges through higher agricultural income, driven by higher sale volume at lower prices. Focusing on high value commodities in rural areas, where arable land is not always fully exploited or utilized, appears to lead to acreage expansion and some crop switching, contributing to higher supply albeit at lower prices. The positive impact on household income is practically significant; it helps improve household food security and asset accumulation. These findings are robust to alternative specifications. Targeted value chain interventions that strengthen and stabilize small‐scale producers' access to markets can contribute to rural poverty reduction via increase in agricultural income.